PENGEMBANGAN AUTHENTIC ASSESSMENT SEBAGAI FUNGSI PENILAIAN FORMATIF PADA PEMBELAJARAN IPS DI KELAS IV SD - Nugroho Nugroho (Universitas Negeri Surabaya, 2017)
ABSTRACTThe objective of this research is to analyze the development results of a valid, reliable, and practical assessment tools in Authentic Assessment as a Function of Formative Assessment In social studies lesson of fourth grade elementary school student. This research is a development research. The development model used in this study is 4D, namely: Define, Design, Develop and Disseminate which refers Thiagarajan development model (1974). The subjects of this research is students of class IV SDN 2 Wonoyoso and SDN Pandanlor Kebumen regency, Central Java. The Product of Authentic Assessment are Scenario Learning, Learning tasks, Instrument of Rating Attitudes, Knowledge, and Skills. The results of this study indicate that the product is the development of Authentic Assessment as a function of formative assessment has (1) validity, (2) reliability, and (3) good practicality when used in social studies lesson in fourth grade elementary school student Semester II, with the theme my environment. Keywords: Authentic Assessment, Formative Assessment, Social Study. ABSTRAKTujuan Penelitian ini adalah untuk menganalisis hasil pengembangan Authentic Assessment Sebagai Fungsi Penilaian Formatif Pada Pembelajaran IPS di kelas IV SD yang valid, reliabel, dan praktis. Penelitian ini merupakan penelitian pengembangan. Model pengembangan yang digunakan dalam penelitian ini adalah 4D, yaitu: Define, Design, Develop, dan Disseminate yang merujuk pada model pengembangan Thiagarajan (1974). Subjek penelitian ini adalah siswa kelas IV SDN 2 Wonoyoso dan SDN Pandanlor Kabupaten Kebumen Jawa Tengah. Produk Authentic Assessment yang dihasilkan meliputi Skenario Pembelajaran, Tugas-tugas Pembelajaran, Instrumen Penilaian Sikap, Pengetahuan, dan Keterampilan. Hasil penelitian ini menunjukkan bahwa Produk berupa pengembangan Authentic Assessment sebagai fungsi penilaian formatif memiliki (1) validitas, (2) reliabiliitas, dan (3) kepraktisan yang baik apabila digunakan pada pembelajaran IPS di Kelas IV SD Semester II, dengan tema Lingkunganku. Kata Kunci: Hasil belajar, IPS, komik, media pembelajaran, pengembangan.